A Test of the Diatom‐Bound Paleoproxy: Tracing the Isotopic Composition of Nutrient‐Nitrogen Into Southern Ocean Particles and Sediments. Issue 10 (25th September 2020) - Robinson, Rebecca S.; Jones, Colin A.; Kelly, Roger P.; Love, Amanda; Closset, Ivia; Rafter, Patrick A.; Brzezinski, Mark
Abstract: Sedimentary nitrogen isotope (as δ 15 N) records from the Southern Ocean provide critical constraints on surface nutrient consumption in the past and the role of Southern Ocean biophysical changes in setting atmospheric p CO2 . We present a field assessment of how surface nitrate consumption is reflected in δ 15 N values of total nitrogen and diatom‐bound nitrogen pools of particles and sediments across the Southern Ocean along 170°W during late austral summer. Mixed layer nitrate δ 15 N values increase northwards associated with greater nitrate drawdown. Particles and sediments are expected to follow this trend. Contrary to expectations, surface ocean particle total nitrogen and diatom‐bound δ 15 N values decreased northward during the late summer, likely due to recycling of nitrogen and the assimilation of regenerated ammonium, as well as nitrate. The relationship between δ 15 N values of the total nitrogen and diatom‐bound pools remains relatively constant across this Southern Ocean transect, suggesting that the isotopic composition of these two surface ocean nitrogen pools are largely set by the δ 15 N value(s) of the assimilated nutrient(s). Surface sediment δ 15 N values do increase away from the region of maximum biogenic silica deposition, suggesting that the recycled nitrogen isotopic signal observed in late summer particles may not significantly impact the sedimentary record. However, the enrichment in δ 15 N values of the diatom‐bound pool is greater than what is expected from progressive utilization of the surface nitrate alone and not yet explained. Plain Language Summary: Southern Ocean biology helps to draw carbon dioxide out of the atmosphere. Here, we present a test of how well the diatom‐bound nitrogen isotope paleoproxy records past surface ocean nutrient conditions, a critical constraint on the role of this biological carbon pump. Overall, the diatom nitrogen pool records the isotopic composition of their source of nutrients. Contrary to expectations, the nitrogen isotopes of the surface ocean particles showed a northward decrease across the Southern Ocean rather than the expected northward increase estimated from the nitrate pool. This is likely due to nitrate and ammonium uptake during the summer rather than growth on nitrate alone. The sedimentary nitrogen pools on the other hand showed an isotope trend more aligned with expectation, but in the case of the diatom‐bound nitrogen, with a steeper gradient. This difference between the water column and the sediments likely stems from sampling during the summer, after the bloom and main sedimentation event, and it suggests that the recycled signal reflects a minor contribution to the overall sedimentary record. Key Points: The isotopic composition of the surface ocean particulate nitrogen pool reflects uptake of dissolved nitrate and ammonium by phytoplankton The isotopic composition of the surface ocean diatom‐bound nitrogen pool parallels the particulate pool Latitudinal trends in sediment diatom‐bound N isotope values are consistent with, but larger than, expected for changes in surface nitrate